The Impact Of Innovation, Brand Image, And A Hedonic Value Lifestyle On The Desire To Purchase An Iphone Smartphone - Pua Merari Br Lubis; Arnita Shintia Sari Sirait; Yuli Elena; Fenny Krisna Marpaung; Juli Meliza (Cita konsultindo, 2024)
The purpose of this research is to study how innovation, brand image, and hedonic factors influence consumer decisions to buy iPhone products. This study involved 69 students from Prima Indonesia University. The analysis used SMART PLS data processing, which helps assess validity and reliability and determine whether each independent variable has a positive or negative impact on the dependent variable. We anticipate that this method will deepen our understanding of the factors influencing students' decisions to purchase iPhones.